Perovskite-Based X-ray Detectors - Chen-Fu Lin; Kuo-Wei Huang; Yen-Ting Chen; Sung-Lin Hsueh; Ming-Hsien Li; Peter Chen (Nanomaterials, 2023)
X-ray detection has widespread applications in medical diagnosis, non-destructive industrial radiography and safety inspection, and especially, medical diagnosis realized by medical X-ray detectors is presenting an increasing demand. Perovskite materials are excellent candidates for high-energy radiation detection based on their promising material properties such as excellent carrier transport capability and high effective atomic number. In this review paper, we introduce X-ray detectors using all kinds of halide perovskite materials along with various crystal structures and discuss their device performance in detail. Single-crystal perovskite was first fabricated as an active material for X-ray detectors, having excellent performance under X-ray illumination due to its superior photoelectric properties of X-ray attenuation with μm thickness. The X-ray detector based on inorganic perovskite shows good environmental stability and high X-ray sensitivity. Owing to anisotropic carrier transport capability, two-dimensional layered perovskites with a preferred orientation parallel to the substrate can effectively suppress the dark current of the device despite poor light response to X-rays, resulting in lower sensitivity for the device. Double perovskite applied for X-ray detectors shows better attenuation of X-rays due to the introduction of high-atomic-numbered elements. Additionally, its stable crystal structure can effectively lower the dark current of X-ray detectors. Environmentally friendly lead-free perovskite exhibits potential application in X-ray detectors by virtue of its high attenuation of X-rays. In the last section, we specifically introduce the up-scaling process technology for fabricating large-area and thick perovskite films for X-ray detectors, which is critical for the commercialization and mass production of perovskite-based X-ray detectors.